2019
DOI: 10.18632/aging.102406
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA PVT1 encapsulated in bone marrow mesenchymal stem cell-derived exosomes promotes osteosarcoma growth and metastasis by stabilizing ERG and sponging miR-183-5p

Abstract: Exosomes secreted by bone marrow mesenchymal stem cells (BMSCs) promote osteosarcoma cell proliferation and migration, while the underlying mechanism remains unknown. Since the long non-coding RNA PVT1 has been reported to be upregulated in osteosarcoma cells and contributes to its growth and metastasis, we aim to investigate whether BMSC-derived exosomes promote osteosarcoma growth and metastasis via transporting PVT1 into osteosarcoma cells. The PVT1 expression in BMSC-derived exosomes was markedly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 42 publications
(48 reference statements)
0
81
0
Order By: Relevance
“…Interestingly, EVs derived from PVT1 knockdown cells negated these effects, thereby highlighting their potential therapeutic application for osteosarcoma. In addition to the direct interaction between PVT1 and ERG, it was confirmed that PVT1 also promoted ERG expression through the sponging of miR-183-5p (Zhao W. et al, 2019).…”
Section: Long Non-coding Rnasmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, EVs derived from PVT1 knockdown cells negated these effects, thereby highlighting their potential therapeutic application for osteosarcoma. In addition to the direct interaction between PVT1 and ERG, it was confirmed that PVT1 also promoted ERG expression through the sponging of miR-183-5p (Zhao W. et al, 2019).…”
Section: Long Non-coding Rnasmentioning
confidence: 78%
“…Similarly, Zhao W. et al (2019) found that the lncRNA PVT1 was enriched in EVs from BM-MSCs. EV-associated PVT1 increased/stabilized the expression of oncogenic protein ERG, which correlated to increased proliferation and migration of osteosarcoma cells in vitro and promoted tumor growth and metastasis in vivo.…”
Section: Long Non-coding Rnasmentioning
confidence: 85%
“…sEV LINC00461 positively modulates BCL‐2 expression by competitively binding to miR‐15a/miR‐16, leading to enhanced cellular proliferation and reduced apoptosis of MM cells 37 . Zhao et al indicated that lncRNA PVT1 could be encapsulated and transferred to osteosarcoma cells in bone marrow MSC‐derived sEV, which promotes tumor growth and metastasis by inhibiting the ubiquitination of ERG protein and sponging miR‐183‐5p 38 …”
Section: Extracellular Vesicle Long Non–coding Rna Mediate Crosstalk mentioning
confidence: 99%
“…Exosomes, extracellular vesicles containing ncRNAs and proteins, are crucial for cellular communication in tumorigenesis in autocrine, paracrine, and endocrine manners [ 147 ]. lncRNAs such as PVT1 and UCA1 can be packaged into exosomes to link the crosstalk between stromal cells and tumor cells partly through autophagy regulation, thereby contributing to pre-metastasis niche formation [ 148 , 149 ]. PVT1 promoted tumor cell metastasis by upregulating autophagy.…”
Section: Cerna-mediated Autophagy and Metastasismentioning
confidence: 99%
“…PVT1 promoted tumor cell metastasis by upregulating autophagy. Moreover, PVT1 was encapsulated into bone marrow mesenchymal stem cells (BMSCs)-derived exosomes and promoted osteosarcoma cell proliferation and migration [ 148 ]. The elevated UCA1 upregulated ATG7 in bladder cancers by sponging miR-582-5p [ 62 ].…”
Section: Cerna-mediated Autophagy and Metastasismentioning
confidence: 99%